Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types. (February 2023) - Wang, Qingling; Luan, Yi; Tang, Ziwei; Li, Zhikun; Gu, Chen; Liu, Rui; Ge, Qingfeng; Yu, Hai; Wu, Mangang
Graphical abstract: Highlights: OSA-starch-stabilized emulsion acted as an active filler to enhance gelation of MP. The filler with smaller and uniform size contributed to a more compact gel network. The filler prompted the conformational change from α -helix to β -sheet in MP gel. Hydrogen bond and hydrophobic interaction in MP gel was enhanced by filler addition. Abstract: Starch-stabilized Pickering emulsions were employed as a novel particulate filler in myofibrillar protein (MP)-based gels for improving the gelling characteristics. The role of emulsions prepared by native starches (NS) with distinctive crystalline types (i.e., A-type waxy corn starch, B-type potato starch, and C-type pea starch) and their OSA-modified counterparts (A-OS, B-OS, C-OS) in the gelling performance was evaluated and compared with MP-stabilized-emulsion. Compared with MP-emulsion, starch-emulsion caused substantial increases in the gelling properties, notably for OSA-starch emulsions. Herein, A-OS exhibited up to 1.26-, 5.3-, and 2.9-fold increments in storage modulus, gel strength, and water holding capacity relative to pure MP gel, respectively, higher than B-OS and C-OS. Moreover, light microscopy evinced a more compact gel network filled with smaller and uniform oil droplets when A-OS emulsions were incorporated into the gels. The addition of OSA-starch emulsions, especially A-OS emulsion, facilitated the protein conformational conversion from α -helix to β -sheet and caused a marked reduction of free sulfhydryls in the gels; yet, the chemical forces that stabilized the gels altered, where remarkable reinforcements in hydrogen bond and hydrophobic interaction were detected, in support of the construction of splendid MP gels. Hence, OSA-starch emulsions show promise as functional components in meat products.